Analysis of Raw Material Inventory Accounting System in Inventory Control at PT Bernofarm Pharmaceutical Company - Andriana Dwi Rahayu; Sri Trisnaningsih (International Journal of Economics, Management and Accounting, 2025)
Inventory management of raw materials is a crucial aspect in the manufacturing industry, particularly in the pharmaceutical sector, as it directly affects the continuity of the production process. This study aims to analyze the raw material inventory accounting system in inventory control at PT Bernofarm Pharmaceutical Company. The methods used include direct observation of operational processes and interviews with management to obtain relevant and accurate data. The results of the study show that PT Bernofarm has implemented an integrated accounting information system within an ERP framework, covering procedures for raw material requisition, issuance, return, and recording of production costs. Each procedure is systematically arranged with clear task separation and is fully computerized. This facilitates internal control and monitoring of raw material flow, while minimizing recording errors. With this effective system, the company is able to avoid both overstocking and stock shortages that could disrupt production. This study is expected to serve as a reference for improving the efficiency and accuracy of raw material inventory management in other pharmaceutical companies.